2010
DOI: 10.1590/s0102-76382010000400023
|View full text |Cite
|
Sign up to set email alerts
|

Os leucócitos e a resposta inflamatória na lesão de isquemia-reperfusão

Abstract: The events of ischemia-reperfusion injury trigger a systemic inflammatory response that can lead to cellular damage and even organ failure. Such effects are noted in the post-operative recovery, especially with the use of cardiopulmonary bypass. Nowadays, we know that leukocytes play an important role in this process. Therefore, this study addresses the role of leukocytes in the pathophysiology of ischemia-reperfusion injury and activation of inflammatory cascades through this process and seeks to help in unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 61 publications
0
14
0
6
Order By: Relevance
“…This leads to multi-system and multi-cell activation and produces a large number of humoral and cellular inflammatory mediators through a cascade reaction, which eventually causes tissue and organ damage or even multiple organ dysfunction syndrome [8-10]. Causes of SIRS also include surgical injury, anesthesia, changes in body temperature, organ ischemia/reperfusion injury, machine blood transfusion, hemodilution, and heparin-protamine complexes [11,12]. It is important to understand the claim of minimal invasion of totally thoracoscopic cardiac surgery apart from the size of the incision.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to multi-system and multi-cell activation and produces a large number of humoral and cellular inflammatory mediators through a cascade reaction, which eventually causes tissue and organ damage or even multiple organ dysfunction syndrome [8-10]. Causes of SIRS also include surgical injury, anesthesia, changes in body temperature, organ ischemia/reperfusion injury, machine blood transfusion, hemodilution, and heparin-protamine complexes [11,12]. It is important to understand the claim of minimal invasion of totally thoracoscopic cardiac surgery apart from the size of the incision.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that protein exudation is more closely related to edema than to other events [33]. These chemical mediators released by the leucocytes and other recruited cells are responsible, for example, for the hypersensitization of nerve fibers, which cause inflammatory pain or hyperalgesia [34].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between neutrophils and the endothelium depends on the action of some integrins and cell adhesion molecules such as ICAM-1 [8]. Chen et al [2] in 2004, demonstrated, through clinical study involving patients undergoing cardiac surgery with CPB, that the release of inflammatory substances during CPB corrupts the transendothelial migration of leukocytes and platelets, with subsequent disordered displacement of these cells to the tissues.…”
Section: Discussionmentioning
confidence: 99%